New elements for an analysis of the dynamics of the secondary classroom - Ferreira, Nuno (2014)
The relevance of the impact of new ICTs on society and everyday life of social actors has allowed sociological analysis to extend its grasp far beyond the obvious features of the network society. Since the incidence of these phenomena intersect with ways of communicating and accessing information, it becomes increasingly reasonable to consider a series of changes and reconfigurations within teaching contexts and, essentially, the pedagogical relationship. The analysis of the secondary classroom must take into account these emerging realities and combine them with existing models. This article proposes widening the sociological debate around school changes, contributing with new analytical features concerning classroom ethongraphy.